Pe PENGEMBANGAN MEDIA PEMBELAJARAN CANVA PECAHAN (CANPEC) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Kurnia, Santi; Yatri, Ika (Jurnal Muara Pendidikan, 2024)
This research aims to develop CANPEC (Canva Pecahan) learning media on the topic of fraction addition and subtraction to improve elementary school students learning outcomes. The research method includes describing the development procedure, validity, and effectiveness of CANPEC learning media. This media was validated by media experts, material experts, language experts, and practitioners with highly valid results, indicating that this media is feasible for use in learning. Implementation of a limited sample showed an improvement in student learning outcomes and student interest in this media. Hypothesis testing results indicate a positive influence of CANPEC on student learning outcomes, with N-Gain test results showing ease of use in learning and positive student responses to this media. CANPEC learning media has proven to be effective and practical in enhancing elementary school students' learning outcomes.